Sistem Informasi Manajemen Terintegrasi: Pengelolaan Order, Arus Kas, dan Otomatisasi Penggajian pada UMKM Konveksi - Slamet Rahayu; R. Rhoedy Setyawan; Yudie Irawan (IDEALIS : InDonEsiA journaL Information System, 2026)
Order tracking, cash flow monitoring, and payroll calculation are still handled manually at many garment Micro, Small, and Medium Enterprises (MSMEs), a practice that leaves considerable room for human error, lost records, and slower administrative processes. This study designs and builds an integrated, web-based management information system tailored for Dims.Collection, examined through a single case study. Development followed the Waterfall model, covering requirements gathering, system design with Unified Modeling Language (UML), coding, verification, and maintenance planning. User permissions for five roles - Administrator, Owner, Sales Staff, Finance Staff, and Human Resources Staff - are managed by a Role-Based Access Control (RBAC) framework to maintain secure system authorization. Ten functional test scenarios were run using Black Box Testing, spanning login authentication, order handling, cash recording, attendance tracking, and automated payroll computation, with every scenario passing (100% success rate). Beyond a working application, this research contributes an RBAC-based business process model that abstracts how order, cash, and payroll functions can be tied together within one centralized-access architecture. Rather than a solution built for one case only, the model is intended to transfer to other MSMEs sharing comparable roles and workflows, functioning as a reusable reference for building access-controlled information systems in the garment sector.